Feed mills for on-farm feed manufacturing - Murphy, James P.; Harner, Joseph P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Quality feed can be manufactured on farm using hammer or roller mills for particle size reduction and volumetric or weighing devices for proportioning ingredients. An understanding of each of the seven steps involved will enhance the ability to manufacture a quality feed for maximum feed efficiency at a feasible price.
Keywords: Swine; Process; Diets